Routledge handbook of contemporary Brunei - Ooi, Keat Gin, 1959-; King, Victor T. (London : Routledge, Taylor & Francis Group, 2023)
"The Routledge Handbook of Contemporary Brunei presents an overview of significant themes, issues, and challenges pertinent to Brunei Darussalam in the twenty-first century. Multidisciplinary in coverage, the contributions cover topics relating to philology, history, religion, language and literature, geography, international relations, economics, politics and sociocultural traditions. The Handbook is structured in eight parts: Foundations History Faith and Ethnicity Literature Language and Education Economics Material Culture Empowerment Chapters focus on the recent past and contemporary developments in this unique country that has remained a Malay Muslim sultanate sustaining its religious and traditional heritage encapsulated in the national philosophy, Melayu Islam Beraja (MIB, Malay Islamic Monarchy). The MIB represents the sultanate's three pillars of social, cultural, political and economic sustainability, and the contributors discuss this concept in relation to the notion of 'Malay' or 'Malaydom', the official religion of the nation-state, Islam and monarchy as the essential system of government. This Handbook is an invaluable reference work for students of Asian and Southeast Asian Studies and researchers interested in the smallest ASEAN state"-- |cProvided by publisher.
Preamble -- Brunei's concerns / Victor T. King and Keat Gin -- I. Foundations -- II. History -- III. Faith and ethnicity-- IV. Literature -- V. Language and education -- VI. Economics -- VII. Material culture -- VIII. Empowerment.
Keywords: Brunei -- Handbooks, manuals, etc